The diagnosis of pancreatic mucinous cystic neoplasm and associated adenocarcinoma in males: An eight‐institution study of 349 patients over 15 years. Issue 7 (17th February 2017) - Ethun, Cecilia G.; Postlewait, Lauren M.; McInnis, Mia R.; Merchant, Nipun; Parikh, Alexander; Idrees, Kamran; Isom, Chelsea A.; Hawkins, William; Fields, Ryan C.; Strand, Matthew; Weber, Sharon M.; Cho, Clifford S.; et al.
Abstract : BACKGROUND: Per WHO, 2000 classification, pancreatic mucinous cystic neoplasms (MCN) are defined by presence of ovarian stroma, and are primarily located in the pancreatic body/tail of females. The incidence of MCN and associated malignancy in males, since, standardization of MCN diagnostic‐criteria is unknown. METHODS: MCN resections from 2000 to 2014 at eight institutions of the Central‐Pancreas‐Consortium were included, and divided into early (2000‐2007) and late (2008‐2014) time‐periods. Primary aim was to characterize MCN and associated adenocarcinoma/high‐grade‐dysplasia (AC/HGD) in males versus females over time. RESULTS: Of 1667 resections for pancreatic cystic lesions, 349 pts (21%) had MCNs: 310 (89%) female, 39 (11%) male. Patients were equally divided between early ( n  = 173) and late ( n  = 176) time‐periods. MCN in male‐patients decreased over time (early: 15%, late: 7%; P  = 0.036), as did pancreatic head/neck location (early: 22%, late: 11%; P  = 0.01). MCN‐associated AC/HGD was more frequent in males versus females (39 vs. 12%; P  < 0.001). The overall rate of MCN‐associated AC/HGD remained stable (early: 17%, late: 13%; P  = 0.4), and was identical in males (39%) over both time‐periods. Males with AC/HGD had more LN‐positive disease versus females (57 vs. 22%; P  = 0.039). CONCLUSIONS: As the diagnostic‐criteria of MCN have standardized over time, MCN diagnosis has decreased in males and head/neck location. Despite this, MCN‐associated adenocarcinoma/high‐grade dysplasia has been stable and remains high in males. Any male with suspected MCN, regardless of location, should undergo resection.